Information and Electronic Transactions Law effects on Malang City people's information-sharing behavior - Hendrawan, Muhammad Rosyihan; Machsunin, Fatich Idamatul (Universitas Padjadjaran, 2024)
In this era, Indonesian society is transitioning to an information society, where technological advances are supported by developments in science, causing a shift in society’s patterns of accessing and disseminating information. The Internet and social media in Indonesia have the potential to expand the public sphere and domains that involve citizens openly. The existence of the Internet and social media public sphere is seen as a space for digital activism, which is a creative means for people to share information and a means to build information democracy by sharing information. Thus, the government's role is to regulate and maintain information order through laws or regulations. This study aimed to evaluate the impact of the Information and Electronic Transactions Law Number 19 of the Year 2016 (Undang-Undang Informasi dan Transaksi Elektronik) on the information-sharing behavior of Malang City’s people on social media. The research method used was correlational with a quantitative approach. Data collection techniques were used on a survey of 350 randomly selected samples. The data analysis used correlational statistical analysis. This study showed that laws and regulations influenced information-sharing behavior on social media in Malang City regarding information and electronic transactions. In conclusion, sharing information with the people of Malang City makes the Information and Electronic Transactions Law a binding legal rule. The remaining research results will be presented in this study.